The Moderating Effect of Abusive Supervision on Religiosity and Whistleblowing Relationship: An Experimental Investigation - Khusnul Jannah; Frida Fanani Rohma; Imam Agus Faisol (Universitas Negeri Semarang, 2023)
Purpose: This study examines the causal relationship between religiosity on whistleblowing. Besides, this study also identifies the moderating role of abusive supervision on the relationship between those two variables. Method: This study used a 2 × 2 between-subjects laboratory experiment with accounting undergraduate students as the subjects. The religiosity is categorized into two levels (high and low). The variable of abusive supervision is manipulated into two levels (high and low). Findings: High religiosity increase whistleblowing. Also, abusive supervision negatively influences whistleblowing. However, abusive supervision moderates the causal relationship between religiosity and whistleblowing. The study demonstrates the significant impact of abusive supervision on an unwillingness to blow the whistle, although the individual is embedded in religious values. Novelty: This study fills a gap in the literature by showing that the tune of the top with a higher hierarchical structure can make an individual's values mingle with the organizational environment and impact his decision to blow the whistle. Furthermore, this research contributes to the conservation of resource theory by providing evidence that superiors have an essential role in molding the behavior of human resources in organizations. Keywords: Abusive Supervision, Decision-Making, Religiosity, Whistleblowing